A sustentabilidade na estratégia de negócio das empresas brasileiras - Nakagawa, Marcus Hyonai (2012)
Objective of this academic research is to analyze sustainability as part of business strategy in companies originally from Brazil. Moreover, research was designed in order to identify the commitment of those companies with sustainable products and services. Theory used as reference focus on issues related to strategy, strategic planning, types of strategy and green economy; all of them here exposed. In addition, sustainability was discussed, as well as sustainable development and its direct relation with mentioned companies. In this context main sustainability indexes related to Brazilian companies studied were considered followed by an explanation of main concepts related sustainable products and services, that should be considered nuclear for companies, the reason why they seek for profit. Link between sustainability and the strategy for those companies was presented through a quantitative analysis made based on what was published at Guia Exame de Sustentabilidade 2011 which information was completed by a market research; that means, two researches were pointed, first one quantitative focus on professionals from sustainability area and the other, qualitative done focus on five experts on that field, whose objective was to detail results from quantitative part. As a result, research pointed that sustainability has not been considered as part of strategy on the majority of Brazilian companies and to do so, it would be necessary to have sustainable products and service in addition of existing processes, index, activities, projects, tasks and sustainable plans